2020
DOI: 10.3390/jpm10040231
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Vascular Changes in Mild Alzheimer’s Disease Patients: Foveal Avascular Zone, Choroidal Thickness, and ONH Hemoglobin Analysis

Abstract: In Alzheimer’s disease (AD), vascular changes could be caused by amyloid beta (Aβ) aggregates replacing the contractile smooth musculature of the arteriole walls. These changes happen in the brain vascular network, but also in the eye, and are related to decreased vascular density and low blood flow. In patients with Alzheimer’s disease, thinning of the choroid and the retina has been shown. The aim of this prospective study was to assess the retinal and choroidal vascular systems, analyzing the choroidal thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…Compared with HC subjects, vessels of AD patients showed lower densities. This condition also occurred in MCI patients [27,28]. Further, we investigated the relationship between microvasculature and retinal thickness.…”
Section: Discussionmentioning
confidence: 86%
“…Compared with HC subjects, vessels of AD patients showed lower densities. This condition also occurred in MCI patients [27,28]. Further, we investigated the relationship between microvasculature and retinal thickness.…”
Section: Discussionmentioning
confidence: 86%
“…There are some doubts about the use of retinal vessel density as a specific biomarker for AD since earlier research on glaucoma confirmed the use of vascular density assessment in the diagnosis and monitoring of POAG. Studies using OCTA in POAG eyes have repeatedly provided evidence of microvascular dropout in the form of a decrease in vessel density within the ONH, the peripapillary retina, and the macula, primarily in the form of a decrease of vascular density in the SVP [ 20 , 57 , 58 ]. The present study quantitatively compared vascular parameters in the eyes of AD and POAG patients and confirmed previous reports that the density of vessels in the individual retinal plexuses are significantly different among AD and POAG groups.…”
Section: Discussionmentioning
confidence: 99%
“…the introduction of OCT angiography (OCTA), a modern technique for non-invasive imaging of retinal blood vessels in vivo, it has been demonstrated that retinal vessel density is significantly reduced in patients with AD, likely due to abnormal Aβ deposits that build up inside blood vessel walls [18][19][20][21]. Latest studies demonstrated significant correlations between retinal vessel density and cognitive function domains [22,23], apolipoprotein E genotype AD [24], and cerebral volumetric changes [25].…”
Section: Competing Interestsmentioning
confidence: 99%
“…Since then, many imaging modalities have been used to detect features that may distinguish AD from controls. Structural changes visible on optical coherence tomography (OCT), such as thinning of the peripapillary and macular RNFL, ganglion cell inner plexiform layer, and choroid, have been linked to mild cognitive impairment (MCI) and AD [ 12 14 ]. One of the main advantages of OCT imaging includes the ability to detect changes in retinal features providing insight into the sequence of events that occur during the development of AD.…”
mentioning
confidence: 99%
“…More recent studies using OCT angiography have shown that changes in the retinal and choroidal vasculature such as enlarged foveal avascular zone are associated with MCI and AD [ 17 , 18 ]. One study found significant choroidal thinning in mild AD while the foveal avascular zone and hemoglobin colorimetric analysis of optic nerve head perfusion did not differ from controls, suggesting that alterations in the choroidal vasculature or structure may occur earlier than the retinal changes associated with AD development [ 14 ]. Additionally, functional changes such as retinal oxygen metabolism and other metabolic alterations have been quantified and shown to be associated with AD using retinal oximetry and fluorescence lifetime imaging ophthalmoscopy [ 19 21 ].…”
mentioning
confidence: 99%